Community Development in the Prevention of Body Shaming in Students in Cisalak Village, Subang - Equatora, Muhammad Ali; Anwar, Umar; Butar-Butar, Herry Fernades; Tando, Cahyoko Edi; Hamzah, Imaduddin; Priyatmono, Budi; Muhammad, Ali; Biafri, Vivi Sylviani; Aulia, Qhistina (Indonesian Journal of Community Services, 2025)
This community service aims to prevent body-shaming behavior among students at SMA Plus Pagelaran, Cisalak Village, Subang, through a community development approach. Body shaming, the act of criticizing a person's physical appearance, hurts students' psychology and self-confidence. This program is implemented by providing education to students, teachers, and parents about the negative consequences of body shaming and the importance of respecting physical diversity.  The activities carried out include socialization, group discussions, and the formation of supportive communities that strengthen students' confidence. The method is a participatory approach that involves all stakeholders in the school environment to create social norms that reject body shaming. Data collected through observation and interviews indicated increased awareness and a shift toward more positive attitudes toward physical differences among students. The results of community service activities prove that community development-based interventions are effective in reducing body shaming and building an inclusive and supportive school environment. This program is expected to serve as a model for preventing body shaming in other rural schools by empowering the community and supporting students' mental well-being. Further implementation can strengthen the role of schools and communities in fostering a positive culture that respects diversity and promotes solidarity among students in Cisalak Village, Subang.